Two oxen ahead : pre-mechanized farming in the Mediterranean - Halstead, Paul. (Hoboken, New Jersey : Wiley-Blackwell, 2014)
"This revealing study shows how careful analysis of recent farming practices, and related cultural traditions, in communities around the Mediterranean can enhance our understanding of prehistoric and Greco-Roman societies. Includes a wealth of original interview material and data from field observation Provides original approaches to understanding past farming practices and their social contexts Offers a revealing comparative perspective on Mediterranean societies' agronomy Identifies a number of previously unrecorded climate-related contrasts in farming practices, which have important socio-economic significance Explores annual tasks, such as tillage and harvest; inter-annual land management techniques, such as rotation; and intergenerational issues, including capital accumulation "--
"Explores annual tasks, such as tillage and harvest; inter-annual land management techniques, such as rotation; and intergenerational issues, including capital accumulation"--
6.6 Mixed Farming: Livestock6.7 Labor, Land, and Livestock: The Domestic Cycle; 6.8 Household and Community; 6.9 Land, Labor, and Livestock in the Past; References; 7 Homo agronomicus? Mediterranean Farming, Present and Past; 7.1 Analogies for the past: "Matters of fact" and "Matters of Interest"; 7.2 Cultural Reason; 7.3 Environmental and Technological Constraints; 7.4 Practical Reason: Costs, Benefits, and Knowledgeable Farmers; 7.5 Ancient Farmers: Knowledgeable and Rational?; 7.6 Farming in the Mediterranean: Analogy and Change; References; Glossary; Index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Agriculture -- Economic aspects -- Mediterranean Region; Farm management -- Mediterranean Region; Land use, Rural -- Mediterranean Region; HISTORY / Ancient / General; Landbouwkunde; Agriculture -- Economic aspects; Farm management; Land use, Rural; Agriculture -- Economic aspects -- Mediterranean region; Farm management -- Mediterranean region; Land use, Rural -- Mediterranean region; Mediterranean Region; Electronic books; Electronic books